Delocalization and Valence Tautomerism in Vanadium Tris(iminosemiquinone) Complexes. (22nd January 2016) - Bendix, Jesper; Clark, Kensha Marie
Abstract: To survey the noninnocence of bis(arylimino) acenaphthene (BIAN) ligands (L) in complexes with early metals, the homoleptic vanadium complex, [V(L)3 ] (1 ), and its monocation, [V(L)3 ]PF6 (2 ), were synthesized. These complexes were found to have a very rich electronic behavior, whereby1 displays strong electronic delocalization and2 can be observed in unprecedented valence tautomeric forms. The oxidation states of the metal and ligand components in these complexes were assigned by using spectroscopic, crystallographic, and magnetic analyses. Complex1 was identified as [V IV (L red )(L . )2 ] (L red = N, N′ ‐bis(3, 5‐dimethylphenylamido)acenaphthylene; L . = N, N′ ‐bis(3, 5‐dimethylphenylimino)acenaphthenesemiquinonate). Complex2 was determined to be [V V (L red )(L . )2 ] + at T <150 K and [V IV (L . )3 ] + at T >150 K. Cyclic voltammetry experiments reveal six quasi‐reversible processes, thus indicating the potential of this metal–ligand combination in catalysis or materials applications.